Alpers disease mutations in human DNA polymerase gamma cause catalytic defects in mitochondrial DNA replication by distinct mechanisms - Qian, Yufeng; Ziehr, Jessica L.; Johnson, Kenneth A. (Frontiers in Genetics, 2015)
The human mitochondrial DNA polymerase gamma (Pol-γ) is nuclearly encoded and is responsible for the replication and repair of the mitochondrial genome. Mutations S305R and P1073L in the POLG gene have been reported to be associated with early-childhood Alpers syndrome. One patient harboring both mutations as compound heterozygous died at 2 years of age after disease onset at 9 months. Quantitative kinetic analysis on purified enzyme showed that the S305R mutation reduces the DNA binding affinity by 10-fold, and reduces the specificity constant (kcat/Km) for correct nucleotide incorporation by 4-fold. It also causes a ~3 fold reduction in the excision rate to remove mismatched nucleotides. Compared to the wild-type Pol-γ, the S305R mutant showed no product formation in a reconstituted rolling circle replisome assay. Interestingly, the P1073L mutant exhibited wild-type activity in single turnover kinetics to quantify changes in kcat/Km, kcat, kexo or processivity, and showed only a 2-fold decrease in the net polymerization rate in the reconstituted replisome assay, while in yeast, P1073L caused a 60-70% mtDNA reduction in haploid cells. The heterozygous diploid yeast cells carrying S305R and P1073L mutations in trans showed ~75% reduction of mtDNA content, relative to homozygous diploid cells with two wild-type alleles. Taken together, we show clearly in both the rolling circle and the humanized yeast system that the P1073L mutation caused significant defects in mtDNA replication, and our results suggest a role for P1073 in the functioning of the polymerase with the mitochondrial DNA helicase, and provide a rationale for understanding the physiological consequences of the S305R/P1073L compound heterozygote in humans.